Calidad De Servicio De Los Usuarios Del Registro De La Propiedad En El Municipio Del Cantón Urdaneta - Garcia Mera, Estefany Michel (2018)
The Property Registry is a public institution whose purpose is the registration, annotation and cancellation of acts and contracts relating to the domain and other real rights on immovable property and identifiable property, the basic function of the Registry is not only to publish acts and contracts but to create entitlements by virtue of an act of public power, this being a place of great concurrence of users who visit their offices to perform the aforementioned procedures.